IMPLEMENTATION OF NUTRITION AND FOOD RIGHTS FOR CHILDREN UNDER THE CARE OF THE BATAM CLASS II SPECIAL CHILDREN'S CARE INSTITUTION - Prayoga, Bayu; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the implementation of nutritional rights for children at the Class II Batam Special Child Development Institution, recognizing that adequate nutrition is a fundamental right for all children, including those in institutional care. The research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation, and analyzed using the policy implementation model of Donald Van Meter and Carl Van Horn. The findings show that the institution has provided basic nutritional services, including regular meals and snacks. However, the overall nutritional status of the children has not yet reached optimal levels, as a significant number still experience malnutrition or overnutrition. This indicates that the existing program has not fully met the nutritional needs of all children. Several key obstacles were identified, including the absence of professional nutritionists, limited budget allocation, inadequate kitchen facilities, overcrowding conditions, and weak coordination among related institutions. These challenges hinder the effective implementation of nutritional programs. In conclusion, the fulfillment of children’s nutritional rights in the institution is still not optimal. Improvements are needed through increased resources, better facilities, the involvement of nutrition experts, and stronger cross-sector coordination to ensure that children receive adequate and balanced nutrition. Keywords: Implementation; Nutritional Rights; Children; Special Child Development Institution Class 2 Batam